(NiZBRANNYE SO^INENIQ W DWUH TOMAH (B/s (N~ASTX (B2s - (NsALTYKOW(B-(N}EDRIN(B, (Nm(B.(Nes ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1984)
(NwO WTOROJ TOM DWUHTOMNIKA IZBRANNYH SO^INENIJ m(B.(Ne(B. (NsALTYKOWA (B- (N}EDRINA WO[EL RQD EGO ZAME^ATELXNYH (B"(NsKAZOK(B" (1883-1886) (NI KNIGA (B"(NpO[EHONSKAQ STARINA(B" (1887-1889), (NZAWER[IW[AQ TWOR^ESKIJ PUTX WELIKOGO RUSSKOGO SATIRIKA(B-(NDEMOKRATA(B.s
rus
Keywords: (NmIFY(B, (NSKAZKI(B, (NfOLXKLORs; (NrUSSKAQ LITERATURAs